2016
DOI: 10.1177/0743558416630808
|View full text |Cite
|
Sign up to set email alerts
|

Communication Between Asian American Adolescents and Health Care Providers About Sexual Activity, Sexually Transmitted Infections, and Pregnancy Prevention

Abstract: Asian American adolescents have been reported to have the lowest amount of communication with health care providers regarding sexual health topics (sexual activity, contraception, sexually transmitted infections, and pregnancy prevention). This study identified Asian American adolescents' attitudes/beliefs regarding how health care providers can be most helpful in communicating about sexual health topics. Twenty participants revealed the following information: (a) confidentiality concerns resulted in lying to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…According to the study by Zhao, Lai, and Flores (2012), Asian-American adolescents believed that their knowledge on sexual health was lacking compared with other adolescent groups. The study indicated that Asian-American adolescents need more education and conversation with health care providers on sex, contraception, STIs, and pregnancy in a place where their privacy is protected from their parents (Zhao et al, 2012). Study participants preferred to have sex education in a private location where they are able to conceal their sexual activities from their parents.…”
Section: Lack Of Knowledge and Information On Sexmentioning
confidence: 95%
“…According to the study by Zhao, Lai, and Flores (2012), Asian-American adolescents believed that their knowledge on sexual health was lacking compared with other adolescent groups. The study indicated that Asian-American adolescents need more education and conversation with health care providers on sex, contraception, STIs, and pregnancy in a place where their privacy is protected from their parents (Zhao et al, 2012). Study participants preferred to have sex education in a private location where they are able to conceal their sexual activities from their parents.…”
Section: Lack Of Knowledge and Information On Sexmentioning
confidence: 95%
“…Despite this general societal assumption, AA youth do participate in risky behaviors such as inconsistent use of condoms and alcohol use with sexual activity (Zhao, Lau, Vermette, Liang, & Flores, 2017). AA emerging adults do not see themselves as being at risk for HIV (Hahm, Lee, Rough, & Strathdee, 2012), even though one in five AAs are infected with HIV (Centers for Disease Control and Prevention [CDC], 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent Asian immigrants to Canada (a country very similar culturally to the U.S.) have more conservative sexual attitudes than long-term Canadian immigrants or Canadian-born Asians (Meston, Trapnell, & Gorzalka, 1998). These conservative sexual attitudes are prominent among East and Southeast Asian families and continue to influence Asian families' ability to openly discuss sexual health today (Lee et al, 2013;Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations